2015
DOI: 10.1159/000440687
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based Stress Reduction (MBSR) as Treatment for Chronic Back Pain - an Observational Study with Assessment of Thalamocortical Dysrhythmia

Abstract: Background: A pilot study of an 8-week mindfulness-based stress reduction (MBSR) program on a sample of low back pain patients was conducted in order to assess the feasibility and effectiveness of the intervention as well as changes in an EEG pattern called thalamocortical dysrhythmia which is associated with chronic pain. Patients and Methods: 22 patients with chronic low back pain participated in an MBSR program. Effect sizes were measured for psychological functioning, pain severity, and quality of life. Fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…In sum, there is no precedent research of forest therapy on CWP. However, in the application of mindfulness based meditation on chronic back pain [ 41 ], the medium size of effect was found for health-related quality of life, depression and pain perception, whereas the large size of effect was found for health-related quality of life in this study. Thus, the effect sizes found in this study are quite compatible to the effects sizes reported in other studies on comparable pain-therapies.…”
Section: Discussioncontrasting
confidence: 71%
“…In sum, there is no precedent research of forest therapy on CWP. However, in the application of mindfulness based meditation on chronic back pain [ 41 ], the medium size of effect was found for health-related quality of life, depression and pain perception, whereas the large size of effect was found for health-related quality of life in this study. Thus, the effect sizes found in this study are quite compatible to the effects sizes reported in other studies on comparable pain-therapies.…”
Section: Discussioncontrasting
confidence: 71%
“…In this paper, we only look at TCD in the specific neurological (i.e., tinnitus, pain, Parkinson’s) and neuropsychiatric (i.e., depression) disorders suggested in the original paper on TCD 9 . Further research has shown that TCD could also be present in schizophrenia 37 , migraines 38 , visual snow 39 , and chronic back pain 40 . Therefore, future research could also look at these additional pathologies and cross-validate our findings by including non-TCD-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…CLBP was the most frequent CP condition studied (n ¼ 6 studies; Ardito et al, 2017;Braden et al, 2016;Cho et al, 2015;Lee et al, 2014;Schmidt et al, 2015;Yuen et al, 2017;Zgierska et al, 2016), followed by fibromyalgia syndrome (FMS; n ¼ 2; Coherence: Treatment group demonstrated increased postintervention cardiac coherence ratio, t(7) Gerdle et al, 2016;Grossman et al, 2017) . In two articles, researchers reported on individuals with CP and an additional primary diagnosis, specifically, posttraumatic stress disorder (Scioli-Salter et al, 2016) and Parkinson's disease (Törnhage et al, 2013).…”
Section: Resultsmentioning
confidence: 99%